Renal ultrastructural alterations induced by various preparations of mefenamic acid - Jarrar, Qais Bashir; Hakim, Muhammad Nazrul; Zakaria, Zainul Amiruddin; Cheema, Manraj Singh; Moshawih, Said (Taylor & Francis, 2020)
Mefenamic acid (MFA) treatment is associated with a number of cellular effects that potentiate the incidence of renal toxicity. The aim of this study is to investigate the potential ultrastructural alterations induced by various preparations of MFA (free MFA, MFA-Tween 80 liposomes, and MFA-DDC liposomes) on the renal tissues. Sprague-Dawley rats were subjected to a daily dose of MFA preparations for 28 days. Renal biopsies from all groups of rats under study were processed for transmission electron microscopic examination. The findings revealed that MFA preparations induced various ultrastructural alterations including mitochondrial injury, nuclear and lysosomal alterations, tubular cells steatosis, apoptotic activity, autophagy, and nucleophagy. These alterations were more clear in rats received free MFA, and MFA-Tween 80 liposomes than those received MFA-DDC liposomes. It is concluded that MFA-DDC liposomes are less potential to induce renal damage than free MFA and MFA-Tween 80 liposomes. Thus, MFA-DDC liposomes may offer an advantage of safe drug delivery.